Corporate social responsibility policies and value creation: does corporate governance and profitability mediate that relationship? - Josua Tarigan; Saarce Elsye Hatane; Linneke Stacia; Deborah Christine Widjaja (Investment Management & Financial Innovations, 2019)
With a purpose to give a deep understanding relating to the manifestation of social responsibilities practices among Indonesian companies, this paper reflects the relationship of corporate social responsibility (CSR), corporate profitability (CP), value creation (VC) and good corporate governance (GCG). Kinder, Lydenberg, and Domini’s (KLD) measurement approach is used in this study to measure the social responsibility practices, as this gives cross-border analysis of social responsibility. Corporate profitability captures return on assets, which is accounting-based measurement, whereas value creation explains the economic value added, which is shareholder-based measurement. Structural Equation Model (SEM) analysis is conducted for Indonesian listed companies, which appeared in Corporate Governance Perception Index (CGPI). The empirical result suggests that CSR serves as a tool in assisting shareholders value and performance. Accordingly, firms should incorporate CSR practices to enhance its strategic investment and sustain a strong relationship with its stakeholders. Subsequently, management should also take concern of having good corporate governance in order to improve company’s performance by supervising and monitoring of the company’s operation, ensure the fulfillment to the stakeholder’s interest. This paper presents fresh insights into applications of corporate social responsibility principles and corporate governance in Indonesian context that has not received systematic attention and consideration in the literature.